The Added Value of Volume-of-Interest C-Arm CT Imaging during Endovascular Treatment of Intracranial Aneurysms - Chintalapani, G. (AJNR Am J Neuroradiol, 2016)
BACKGROUND AND PURPOSE: Successful endovascular treatment of intracranial aneurysms requires understanding the exact relationship of implanted devices to the aneurysm, parent artery, and other branch vessels during the treatment. Intraprocedural C-arm CT imaging has been shown to provide such information. However, its repeated use is limited due to increasing radiation exposure to the patient. The goal of this study was to evaluate a new volume-of-interest C-arm CT imaging technique, which would provide device-specific information through multiple 3D acquisitions of only the region of interest, thus reducing cumulative radiation exposure to the patient. MATERIALS AND METHODS: VOI C-arm CT images were obtained in 28 patients undergoing endovascular treatment of intracranial aneurysms. VOI images were acquired with the x-ray source collimated around the deployed device, both horizontally and vertically. The images were reconstructed by using a novel prototype robust reconstruction algorithm to minimize truncation artifacts from double collimation. The reconstruction accuracy of VOI C-arm CT images was assessed quantitatively by comparing them with the full-head noncollimated images. RESULTS: Quantitative analysis showed that the quality of VOI C-arm CT images is comparable with that of the standard Feldkamp, Davis, and Kress reconstruction of noncollimated C-arm CT images (correlation coefficient = 0.96 and structural similarity index = 0.92). Furthermore, 91.5% reduction in dose-area product was achieved with VOI imaging compared with the full-head acquisition. CONCLUSIONS: VOI imaging allows multiple 3D C-arm CT acquisitions and provides information related to device expansion, parent wall apposition, and neck coverage during the procedure, with very low additional radiation exposure to the patient.